Locomotion and posture development in immature male and female rats (Rattus norvegicus): Comparison of sensory-enriched versus sensory-deprived testing environments - Swann, Hillary E; Brumley, Michele R (Journal of comparative psychology (Washington, D.C. : 1983), 2019)
The aim of the current study was to provide normative data on spontaneous locomotion and posture behavior in developing rats (Rattus norvegicus), during the first 2 postnatal weeks. Male and female rat pups were tested daily from P1 (postnatal day 1; ∼24 hr after birth) to P15 in a sensory-enriched or sensory-deprived testing environment, which was enclosed in a temperature-controlled incubator. Pups in the sensory-deprived condition were tested individually and placed in a square, Plexiglas box (open-field) for a 20-min test period. Pups in the sensory-enriched condition were placed in the same box with the siblings and bedding from the home cage to provide sensory stimulation that mimicked the home nest. Subjects in this condition were tested two at a time, with an additional two siblings (2 males and 2 females total in box). It was hypothesized that pups in the sensory-enriched testing condition would demonstrate more mature patterns of behavior, given the presence of behavior-activating sensory stimuli in the box. It was found that rat pups exhibited spontaneous pivoting and crawling as early as P1, regardless of sensory stimulation present in the testing environment. These behaviors were shown at least 1 to 3 days earlier than reported in prior studies. Quadrupedal walking occurred as early as P4 but was not reliably expressed until P10/11. These findings suggest that controlling temperature during testing influences the typical age of first occurrence of these behaviors. Finally, there were no sex differences in the duration of locomotion and posture behaviors. (PsycINFO Database Record (c) 2019 APA, all rights reserved).